2020
DOI: 10.2514/1.j059100
|View full text |Cite
|
Sign up to set email alerts
|

Wavenumber-Based Impedance Eduction with a Shear Grazing Flow

Abstract: While intrinsic by definition, the impedance measured by impedance eduction has been shown to depend on the direction of the incident waves relative to the mean flow. The purpose of the present work is to evaluate whether part of the observed differences could stem from a biased wavenumber definition made during the impedance eduction process.Comparisons are made between the results of impedance eductions with uniform flow and the Ingard-Myers boundary condition, with the 1D linearized Euler equations and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In fact, for low Mach numbers and Helmholtz numbers, it is possible to show that ζ ≈ βM by comparing Eqs. ( 6) and (8), which is confirmed in Fig. 9.…”
Section: Educing Additional Parameterssupporting
confidence: 73%
See 1 more Smart Citation
“…In fact, for low Mach numbers and Helmholtz numbers, it is possible to show that ζ ≈ βM by comparing Eqs. ( 6) and (8), which is confirmed in Fig. 9.…”
Section: Educing Additional Parameterssupporting
confidence: 73%
“…However, Weng et al [4] concluded that viscosity is not able to account for the discrepancy between upstream and downstream and collapse the educed impedances onto one value per frequency, while Nark et al [7] found that small corrections to the mean flow velocity were sufficient to collapse the upstream and downstream educed impedances. More recently, Roncen et al [8] concluded that this inconsistency is still present even when considering a three-dimensional inviscid sheared flow profile and no-slip condition at the lined wall, suggesting the liner physics are still not fully captured. With this is mind, novel boundary conditions have been introduced in the past years by including an additional parameter to better describe the liner physics [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in impedance when using upstream or downstream acoustic sources with both in-situ and impedance eduction techniques may arise from different reasons. In the case of impedance eduction, the flow is assumed as uniform, which may introduce a significant error especially for upstream acoustic propagation 40 i.e. when using a downstream acoustic source.…”
Section: Grazing Incidence Impedance Measurementsmentioning
confidence: 99%
“…It basically consists in building an eigenvalue problem and solving it on arbitrary geometries, with or without flow and/or impedance boundary conditions. The generalized eigen problem is solved with an Arnoldi's method [21].…”
Section: Infinite Duct 1d Casementioning
confidence: 99%